(untitled) (Research, Society and Development, 2020)
Introduction: The control of blood pressure occurs through the interaction between the autonomic nervous system and substances secreted by different types of cells, including endothelial cells, causing changes in any of these mechanisms to lead to the development of arterial hypertension. The practice of physical exercises is shown as a non-pharmacological treatment capable of significantly reducing both systolic and diastolic blood pressure, attenuating pressure reactivity and increasing the bioavailability of nitric oxide. Objective: The objective of this critical review is to carry out a bibliographic survey of the main studies on interval exercises, pressure reactivity and nitric oxide. Methodology: Articles with such themes were selected and then classified into categories with the definitions of the concepts. Conclusion: Therefore, interval training is suggested to promote changes in vascular reactivity and nitric oxide concentrations will depend on the intensity and volume.